The Influence of Incentives, Competencies, and Work Facilities on Professionalism With Implications for Employee Performance at the Regional Revenue Office of Tanjung Jabung Barat District - Pantun Bukit; Osrita Hapsara; Sri Jahara (Dinasti Publisher, 2024)
This research aims to analyze the influence of incentives, competencies, and work facilities through professionalism on employee performance at the Regional Revenue Office (Bapenda). The method used in this research is descriptive-verification and quantitative method. Based on the approach, the sample size is determined to be 66 people. This research uses the PLS analysis method. Based on the research results, Incentives (X1), Competencies (X2), and Work Facilities (X3) have a significant simultaneous effect on Professionalism (Y). Furthermore, Incentives (X1), Competencies (X2), and Work Facilities (X3) partially have a significant effect on Professionalism (Y). Incentives (X1), Competencies (X2), and Work Facilities (X3) have a significant simultaneous effect on Employee Performance (Z). Furthermore, Incentives (X1), Competencies (X2), and Work Facilities (X3) partially have a significant effect on Employee Performance (Z). Professionalism (Y) has a significant simultaneous effect on Employee Performance (Z).